Area Design of Keyboard Layout for Comfortable Texting Ability with the Thumb Jacobian Matrix. Issue 10 (15th June 2022) - Xiong, Le; Fu, Chenglong; Deng, Shiming
ABSTRACT: The objective of this paper is to develop a theory for designing the keyboard area of smartphones, and endowing the users with comfortable texting ability via one thumb. In light of the fact that most users tend to hold the smartphone in one hand and manipulate with one thumb in daily life, this paper extracts the thumb kinematic chain from the thumb anatomy of the human hand, and defines the manipulation comfort ellipsoid of the thumb. Then some indexes such as the morphology and volume of the comfort ellipsoid, and the condition number of the thumb Jacobian are presented to evaluate the manipulation comfort of the thumb. Finally, the design problem of the smartphone's keyboard area is transformed into an optimization problem that determines the most comfortable manipulation space for the human thumb. The proposed quantitative study method of the thumb manipulation comfort is verified by 12 subjects who hold a smartphone with one hand and manipulate the screen with one thumb, and the most comfortable keyboard layout of smartphone is determined for the 12 subjects. The proposed method for the manipulation comfort of the human thumb bridges the gap between the layout planning of soft keyboard of smartphones and the comfort of single thumb manipulation.